The Use of Post-ablation Stimulated Thyroglobulin in Predicting Clinical Outcomes in Differentiated Thyroid Carcinoma – What Cut-off Values Should We Use?. Issue 2 (February 2019) - Wong, K.C.W.; Ng, T.Y.; Yu, K.S.; Kwok, J.S.S.; Chan, K.C.A.; Suen, J.J.S.; Leung, S.F.; Chan, A.T.C.
Abstract: Aims: Recently published international guidelines recommended using the stimulated thyroglobulin (sTg) post-radioactive iodine (RAI) ablation, in conjunction with tumour stage, as a risk stratification factor. The choice of cut-off values for sTg, namely 1 and 10 ng/ml, was, however, largely based on the functional sensitivities of the assays used, with relatively few published data addressing the prognostic impact of alternative cut-off values. Our study aims to provide data on the prognostic value of sTg at different levels of sensitivities and specificities. Materials and methods: We conducted a retrospective review of all adult cases of differentiated thyroid carcinoma receiving RAI ablation at our centre from 2008 to 2010. All patients had sTg measured at around 6 months post-ablation. The functional sensitivity of our assay was 0.5 ng/ml. The outcome was adverse clinical event, defined as cancer-related death, persistent macroscopic disease demonstrable on imaging (including radioisotope scan) and/or receiving further treatment for persistent or recurrent disease. A receiver operating characteristic (ROC) analysis was carried out. Results: We identified 140 patients treated in the review period, with 106 of them suitable for further analysis. The reasons for exclusion included the presence of anti-thyroglobulin antibodies and medullary or anaplastic histological subtypes. Most (54.7%) had intermediate-risk disease as per the American Thyroid Association classification (2009). The median follow-up duration was 6.4 years; the minimum, excluding deaths, was 5.0 years. ROC analysis showed that the optimal cut-off value of sTg for predicting adverse clinical events was >1.0 ng/ml, associated with a sensitivity of 90.9%, a specificity of 81.0%, a positive predictive value of 55.6% and a negative predictive value of 97.1%. Conclusion: Based on ROC analysis of sensitivities and specificities, our data showed that a post-ablation sTg value of 1 ng/ml is the optimal cut-off in prognostication of adverse clinical events. Highlights: Previous studies dichotomised thyroglobulin levels into detectable or undetectable. Receiver operating characteristic analysis was carried out. The most prognostic post-ablation stimulated thyroglobulin level was >1.0 ng/ml. This level was an independent prognostic factor in multivariate analysis. Our results validated the cut-off levels recommended in recent guidelines.